Blood biomarkers in epilepsy - Banote, Rakesh Kumar; Akel, Sarah; Zelano, Johan (Acta neurologica Scandinavica, 2022)
Robust and accessible biomarkers are greatly needed in epilepsy. Diagnostic and prognostic precision in the clinic needs to improve, and there is a need for objective quantification of seizure burden. In recent years, there have been advances in the development of accessible and cost‐effective blood‐based biomarkers in neurology, and these are increasingly studied in epilepsy. However, the field is in its infancy and specificity and sensitivity for most biomarkers in most clinical situations are not known. This review describes advancements regarding human blood biomarkers in epilepsy. Examples of biochemical markers that have been shown to have higher blood concentrations in study subjects with epilepsy include brain proteins like S100B or neuronal specific enolase, and neuroinflammatory proteins like interleukins, and tumor necrosis factor‐alpha. Some of the blood biomarkers also seem to reflect seizure duration or frequency, and levels decrease in response to treatment with antiseizure medication. For most biomarkers, the literature contains seemingly conflicting results. This is to be expected in an emerging field and could reflect different study populations, sampling or analysis techniques, and epilepsy classification. More studies are needed with emphasis put on the classification of epilepsy and seizure types. More standardized reporting could perhaps decrease result heterogeneity and increase the potential for data sharing and subgroup analyses.